(untitled) (Nordic Journal of Practical Theology, 2024)
Rituals are a way to express both personal and relational emotions. The COVID-19 pandemic disrupted funerals around the world. Although the pandemic was not very severe in Finland, the restrictions on organizing and attending funerals were quite strict. This article seeks to uncover what kinds of emotions participants experienced when organizing and attending funerals during COVID-19, as well as what these emotions may reveal regarding funerals during a pandemic. The 45 letters that form the qualitative data of the research offer some important real-time insights into how funeral practices were experienced during the pandemic. Thematic analyses revealed the following main themes: irritation when organizing a funeral, contradictory emotions about attending a funeral, embodiment of emotions, and funeral ritual as a channel of meaning. The strongest negative emotions were directed towards the restrictions, rather than being the type of painful emotions normally connected with funerals and bereavement. Even though the letters focused on funerals, they additionally revealed reflections on the pandemic. This shows that the funeral acted both as a normal life cycle ritual and as a disaster ritual, which helped the writers to cope with the pandemic itself.